STRICT LIABILITY: A SOLUTION TO HOLD PEATLAND DESTROYERS ACCOUNTABLE - Bayu Novendra; Kania Jennifer Wiryadi (Sociae Polites, 2020)
In 2019, burned forests and peatlands reached 328 thousand hectares. The World Bank estimates that total loss from this event reached 5.2 billion USD. At least, until September 2019, there were 900,000 residents who experienced respiratory health problems and hundreds of schools in Indonesia, Malaysia and Singapore had to stop teaching and learning activities due to the haze. One of the factors that ‘fertilizes’ problems for destruction of forests and peatlands that continue to grow is difficulty to account the perpetrator. This paper will attempt to answer and solve these problems with the concept of strict liability. This research will answer two problems, how can the concept of strict liability solve the issues for peatland law enforcement? And how does the application of strict liability rules compare with Netherlands and United States? The government has pursued a moratorium policy. Starting from Presidential Instruction (Inpres) No. 10 year 2011 and extended by Inpres No. 6 year 2013 also Inpres No. 8 year 2015. However, this policy is considered unsatisfactory because there are still forestry and plantation permits issued by the government and massive forest and land burning. Therefore, there needs a solution from a repressive approach to provide a deterrent effect on forest fire perpetrators. Strict liability concept means that the defendant will still be responsible even though his activities were lawful and carried out carefully. Furthermore, strict liability is an accountability that not only eliminates elements of subjective error, but also objectively. Some countries have practiced strict liability, namely the Netherlands and the United States. Keywords: Forest Fire, Law Enforcement, Moratorium, Peatland, Strict Liability